Educational Achievements of First and Subsequent Generation Learners in East Delhi/Ncr Region in India - A Comparative Study - Pandey, Ashok; Singh, Binod Kumar (Asian Development Policy Review, 2015)
The present paper aims to find out the differences between study habits and the academic achievement of the rural and urban first generation learners and subsequent generation learners. For this study, 16 schools from East Delhi/ NCR have been selected based on the convenience sampling. From each school 20 students have been selected and out of which 10 are first generation learners and 10 are subsequent generation learners. The tool used in this paper was developed by Palsane and Sharma (1989) and named as Study Habit Inventory (SHI). The study found that there is a significant difference between study habits as well as the academic achievements of rural and urban first generation learners and subsequent generation learners. The result of this study has an implication for not only teachers, but also for students and parents. The teachers in the classroom are confronted with the development of potentialities and academic ability of students, which is totally dependent upon teacher efficiency.